2020
DOI: 10.1155/2020/7879629
|View full text |Cite
|
Sign up to set email alerts
|

VX765 Attenuates Pyroptosis and HMGB1/TLR4/NF-κB Pathways to Improve Functional Outcomes in TBI Mice

Abstract: Background. Traumatic brain injury (TBI) refers to temporary or permanent damage to brain function caused by penetrating objects or blunt force trauma. TBI activates inflammasome-mediated pathways and other cell death pathways to remove inactive and damaged cells, however, they are also harmful to the central nervous system. The newly discovered cell death pattern termed pyroptosis has become an area of interest. It mainly relies on caspase-1-mediated pathways, leading to cell death. Methods. Our research focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 73 publications
4
45
0
Order By: Relevance
“…In the present study, external administration of DI effectively reduced NLRP3 inflammasome activation and subsequently inhibited NLRP3-mediated GSDMD cleavage, further emphasizing the inhibitory effect of DI on pyroptosis. The previous studies performed by our group highlighted the importance of inhibiting the NLRP3 inflammasome in order to achieve neural functional recovery from traumatic injury and ischemia stroke ( 41 43 ). DI may possess significant potential as a neuropathological drug for promoting neurological functional recovery due to its strong inhibitory activity against NLRP3-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, external administration of DI effectively reduced NLRP3 inflammasome activation and subsequently inhibited NLRP3-mediated GSDMD cleavage, further emphasizing the inhibitory effect of DI on pyroptosis. The previous studies performed by our group highlighted the importance of inhibiting the NLRP3 inflammasome in order to achieve neural functional recovery from traumatic injury and ischemia stroke ( 41 43 ). DI may possess significant potential as a neuropathological drug for promoting neurological functional recovery due to its strong inhibitory activity against NLRP3-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide‐binding oligomerization domain (NOD)‐like receptor (NLR) pyrin domain‐containing (NLRP) inflammasomes activate the cleavage of pro‐interleukin‐1β (pro‐IL‐1β) and pro‐IL‐18, based on caspase‐1 and trigger pyroptosis (Huang et al, 2020). Recently, it was reported that pyroptosis is widespread in diseases of the central nervous system, which is involved in the repair, aging, tumor, cerebral hemorrhage, and ischemia of the central nervous system (Huang et al, 2020; Q. Li et al, 2020; Sun et al, 2020). However, the precise role of pyroptosis and related regulation drugs in SAH has not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the role of autophagy and pyroptosis in IDD, a rat disc IDD model was designed and conducted by needle puncture. VX-765, a caspase-1 inhibitor, which could efficiently decrease cell pyroptosis, was used in our animal model [ 27 ]. Degenerative NP tissues were marked by loss of ECM proteins and replaced by fibrous tissues.…”
Section: Resultsmentioning
confidence: 99%